2017
DOI: 10.1364/josaa.34.000224
|View full text |Cite
|
Sign up to set email alerts
|

Local normal vector field formulation for periodic scattering problems formulated in the spectral domain

Abstract: We present two adapted formulations, one tailored to isotropic media and one for general anisotropic media, of the normal-vector field framework previously introduced to improve convergence near arbitrarily shaped material interfaces in spectral simulation methods for periodic scattering geometries. The adapted formulations enable the definition and generation of the normal-vector fields to be confined to a region of prolongation that includes the material interfaces but is otherwise limited. This allow for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…(4) yields poor convergence since it violates the Li-rules (1996). We propose to use a normal-vector field approach (Popov and Nevire 2001; Beurden and Setija 2017). In Dilz et al.…”
Section: Efficient Field-materials Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…(4) yields poor convergence since it violates the Li-rules (1996). We propose to use a normal-vector field approach (Popov and Nevire 2001; Beurden and Setija 2017). In Dilz et al.…”
Section: Efficient Field-materials Interactionmentioning
confidence: 99%
“…(2017) it is shown that when the Li-rules are satisfied, good convergence is reached in a continuous spectral discretization in a formulation similar to the RCWA formulation by Granet and Guizal (1996). We follow the same approach as Popov and Nevire (2001), Beurden (2011, 2012), Beurden and Setija (2017), van Beurden (2013) in constructing normal-vector fields and the following is intended as a short summary of that method.…”
Section: Efficient Field-materials Interactionmentioning
confidence: 99%
See 3 more Smart Citations